The vernacular portuguese distich in the poetical translation of the epistle phyllis demophoonti from Ovid’s Heroides - Melo, João Victor Leite (2020)
To translate the Latin elegiac couplet, some metrified poetic translations of Ovidian works into Portuguese have shown a preference for the vernacular couplet created by Péricles Eugênio da Silva Ramos (1964). This couplet is formed by combining one Alexandrine verse followed by a decasyllable. Following this model, we present our proposal of a creative transposto of the letter of Phyllis to Demophoon (Ep. 2), based on the considerations of some poet translators that used the same arrangement and on the theoretical and methodological basis of the practice of poetic translation according to Roman Jakobson (1969), Samuel Levin (1978) and José Paulo Paes (2008).